Industrial systems analysis and design on Filbar's and Company, Inc. - Dy, Glady; Francisco, Reynald; Sumalabe, Mrian; Vargas, Vina Vivien (College of Engineering, 2005)
Filbar's is considered the largest retailer, wholesaler and distributor of US comics, local and foreign magazines, pocketbook bestsellers and Tagalog pocketbooks in the Philippines. While it aims to maintain and operate the largest and strongest network of distribution infrastructure nationwide, Filbar's must capture a much greater market share, maintain its present customers, and keep their reputation at its best. This Total Systems Study was conducted to improve the present system of Filbar's. The company maintains 35 branches nationwide and provides to different wholesalers, franchisees, and consignees nationwide, although the market is concentrated in the Metro Manila Area. They provide to almost all types of customers (while targeting the ABC market) and get most of the profit from selling back issues of local magazines (50% of profit). The design of Filbar's systems framework was discussed and different tools were used to analyze the company's strengths, weaknesses, opportunities and threats considering the macro- and micro- environments, as well as its internal position. Environmental scanning showed that the major considerations in the company's strategy formulations are tax reforms, GNP growth, inflation rates, and % expenditure n non-food items. Also, technological factors were considered such as the popularity of SMS messaging and other developments in communication, the prevalence of outsourcing of logistics management, and the breakthrough of the internet as a business tool. The environment of the industry was discussed in detail using Porter's Five Forces Model while the industry analysis showed that there is an increasing trend in the magazine industry and Filbar's company has the greatest share as of this moment. The competitor analysis showed that Comic Quest is Filbar's greatest competitor although the competition is far from being intense (as shown in the competitor's matrix of competitive advantage). The SWOT matrix revealed that the best strategy for Filbar's is to expand by offering attractive packages to potential franchisees and to increase the number of branches in Visayas and Mindanao, as well as some areas of Luzon. It was also recommended that Filbar's maintain a good tracking system and forecasting method for their products. These were discussed further in the Gap Analysis. The Gap Analysis suggested that in order for the company to close the gap between its current strategies and its goals, Filbar's should do the following: advertise through flyers, tag-lines, larger price tags with Filbar's logo, development of key result areas and key performance measures; sales monitoring and data keeping, forecasting, insertion of leaflets in magazines advertising Filbar's subscription offers, research, advertising, promotions, market analysis, and production efficiency studies. Using the Strategy Prioritization Matrix, it was seen that the strategies that Filbar's must focus on to close the gap were subscription, forecasting, performance measures, and Filmax BOP. In-line with the results in the SWOT matrix, it was recommended that Filbar's should continue on entertaining franchises and consignments and treat Filmax as a different entity. Instead of focusing solely on increasing solely the number of business centers of Filmax, the company should be able to provide attractive marketing packages to potential subscribers, franchisers and consignees. This, in turn could result to the increase of number of Filbar's branches that could be seen nationwide, which is in-line with the company's vision, mission, and goal of having a solid nationwide distribution. Also, to be able to stay as the market leader in the distribution of reading materials in the country, Filbar's must create performance measures wherein they would be able to assess their position in the industry, as well as its internal position at any given time. Furthermore, the application of weighted average method of forecasting was recommended for the company to be able to meet its demand and to be able to control its inventory for the control of holding costs. Implementation guidelines were discussed to help the company measure its ability and willingness to employ the said recommendations.